2015
DOI: 10.3892/ijmm.2015.2251
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human lactoferrin enhances the efficacy of triple therapy in mice infected with Helicobacter pylori

Abstract: Helicobacter pylori (H. pylori) is a life-threatening pathogen which causes chronic gastritis, gastric ulcers and even stomach cancer. Treatment normally involves bacterial eradication; however, this type of treatment only has a rate of effectiveness of <80%. Thus, it is a matter of some urgency to develop new therapeutic strategies. Lactoferrin, a member of the transferrin family of iron-binding proteins, has been proven to be effective in removing a vast range of pathogens, including H. pylori. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In particular, after the pioneering study by Miehlke and colleagues [ 289 ], who demonstrated the in vitro bactericidal activity of rhLf against 13 clinical isolates of H. pylori , both bLf and rhLf were shown to promote bacterial growth and gastric inflammation in mice [ 290 ]. In the same field, inconclusive results have been obtained so far in humans, with two open randomized trials showing the efficacy [ 291 , 292 ] and one the inefficacy [ 293 ] of bLf in improving eradication rates of H. pylori when applied in combination therapies. Moreover, despite the abovementioned studies proving the efficacy of Lf on animal models of colitis, the failure of bLf in decreasing risk of sepsis and necrotizing enterocolitis (NEC) in preterm infants was recently reported [ 294 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, after the pioneering study by Miehlke and colleagues [ 289 ], who demonstrated the in vitro bactericidal activity of rhLf against 13 clinical isolates of H. pylori , both bLf and rhLf were shown to promote bacterial growth and gastric inflammation in mice [ 290 ]. In the same field, inconclusive results have been obtained so far in humans, with two open randomized trials showing the efficacy [ 291 , 292 ] and one the inefficacy [ 293 ] of bLf in improving eradication rates of H. pylori when applied in combination therapies. Moreover, despite the abovementioned studies proving the efficacy of Lf on animal models of colitis, the failure of bLf in decreasing risk of sepsis and necrotizing enterocolitis (NEC) in preterm infants was recently reported [ 294 ].…”
Section: Discussionmentioning
confidence: 99%
“… 48 It has also been shown that recombinant human lactoferrin can bind and disrupt some bacterial cell membranes, 49 , 50 and when it is co-administered with amoxicillin against Gram-negative bacteria it increases its efficacy, as found in animal models. Furthermore, in a recent study Yuan et al 51 examined the effectiveness of recombinant human lactoferrin isolated from transgenic goats as a treatment for H. pylori in vitro and in vivo . For the in vitro experiments, the results revealed that recombinant human lactoferrin not only inhibited the growth of H. pylori , but also suppressed the expression of two major virulence factors, cagA and vacA .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lf as a single component failed to eradicate the H. pylori infection but in combination with triple esomeprazole, clarithromycin and amoxicillin therapy and with probiotics, favored the resolution of infection and ameliorated the inflammatory response more effectively than in combination with two-antibiotic treatment, as described in experimental mice treated with r-hLf from transgenic goats, and also in trails of patients treated with native bLf. Interestingly, r-hLf not only inhibited the growth of H. pylori , but also suppressed the expression of two of its major virulence factors [133,134]. …”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%